489 Interleukin Phenotype in Patients with Pfapa. (October 2012) - Iurian, SI; Dobrota, L; Iurian, S; Neamtu, ML; Bera, L; Rosenberg, A
Abstract : Background: PFAPA is a chronic condition including recurrent fever episodes, aphthous stomatitis, pharyngitis, adenitis. According to a previous study, even between febrile attacks, there is increasing of pro-inflammatory mediators. Aims: To evaluate serum interleukin phenotype between febril episode in PFAPA patients from our clinic; To establish correlation between C reactive protein (CRP) and pro-inflammatory interleukins: tumor necrosis factor-alpha (TNFα), interleukin-8 (IL-8); To evaluate link between CRP and anti-inflammatory interleukins: interleukin-10 (IL-10); To identify a sensitive biological marker to estimate PFAPA evolution. Methods: Authors analyzed 2 groups: "PFAPA group" represented by 6 patients and "control group" containing 4 no-PFAPA patients. Inclusion citeria: patients up to 10 years of age that fulfilled PFAPA diagnosis criteria; patients between febrile attacks; negative procalcitonin (PCT) blood value in order to exclude bacterial infections for study patients. Exclusion criteria: patients during febrile attacks. Both groups patients were tested for serum levels of PCT, CRP, IL-8, TNFα, IL-10. Data was statistically analyzed using independent "t" test. Results: Both group patients have normal serum levels for interleukins 8/10 and high TNFα values. Mean value for TNFα was 11.26 pg/ml in PFAPA group and 13.2 pg/ml in no-PFAPA group. Regarding CRP values, mean value for PFAPA patients was 19.72 (range between 2.4–95) as compare to 5.04 in no-PFAPA patients. Conclusions: TNFα, IL-8, IL-10 aren't useful to appreciate PFAPA evolution pattern. CRP remains a sensitive marker for disease activity in PFAPA patients, even out of fever attacks. Our study didn't confirm previous study data.